PERCEPTIONS AND IMPACTS OF THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN DEEP LEARNING AMONG PAI STUDENTS - Nanang Ilham Fatih; Nafila Mubarokah; Fanazal Risqianto; Laela Hanifah; Ma’mun Hanif (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2026)
Abstract : Advances in Artificial Intelligence (AI) have brought significant changes to the world of education, including the Islamic Religious Education (PAI) program. The use of AI has the potential to support deep learning through easier access to information, personalized learning, and increased learning efficiency. However, research on the use of AI in the context of deep learning for PAI students remains limited. This study aims to analyze the perceptions and impacts of AI utilization in supporting deep learning among PAI students. The study employs a qualitative approach using the case study method. The research participants consisted of 20 active students in the PAI program who had used AI in their academic activities and were selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and drawing conclusions. Data validity was ensured through source triangulation and member checking. The results show that all respondents have used AI in their learning. Most students believe that AI helps them understand course material, speeds up the completion of assignments, facilitates the search for references, improves the efficiency of study time, and supports their motivation to learn. Additionally, AI helps students obtain explanations that are more concise and easier to understand. However, the use of AI also faces several challenges, such as limited internet connectivity, the need to verify the accuracy of information, restricted access to certain features, and the potential for overreliance on technology. This study concludes that AI has a positive impact on supporting in-depth learning among PAI students; however, its use must be approached wisely and critically, while maintaining academic ethics and recognizing the role of instructors as primary mentors in the learning process. Keywords:. Artificial Intelligence; Deep Learning; Islamic Education Students; Student Perceptions